Análise fitoquímica e estudo das atividades antimicrobiana, antioxidante e de inibição da enzima acetilcolinesterase da espécie Helietta apiculata Benth - Fernandes, Tanize Stuker (2011)
The phytochemical research of crude extract of the bark metanólico and stem fractions of Helietta apiculata Benth, Rutaceae, led to the isolation of four alkaloids furoquinoline (γ-fagarine (9), Maculine (24), Kokusaginine (17) and Isodictamnine (11)), a limonoids known as Limonin (42), a coumarin called Chalepin (27), two derivatives of cinnamic acid in mixture, 4-hydroxy-3,5-dimetoxicinamato methyl (69) and 3, 4, 5- trimetoxicinamato methyl (55), In addition to a mixture of three neolignans (T26). Through the hidrodestilação was the extraction of essential oils of the species H. apiculata in different seasons, with the aim of comparison of chemically the same as seasonality. Being that the main constituents were the gifts, the elemeno, γ-elemol, elemol and espatulenol. While limonene was not biosynthesized during the spring, being present in significant quantities in summer, autumn and winter. The crude extract, fractions and isolated substances were tested as to their antimicrobial, antioxidant activity and inhibition of the enzyme Acetylcholinesterase. When tested against microbial agents, metabolites γ-fagarine, limonin, isodictamnine, derivatives of cinnamic acid and neolignans mixture on demonstrated antimicrobial activity. When testing the antioxidant potential through screening substances γ-fagarine, isodictamnine and maculine, neolignans were more active as antioxidants. To test the ability of inhibition of the enzyme Acetylcholinesterase none of isolated proved with substantial potential inhibitor, since they do not have overcome the pMIQ threshold value of 10,5 established as required value for a substance to be considered such inhibiting enzyme.